MODERN ASPECTS OF ORGANIZING PHYSICAL EDUCATION LESSONS IN HIGH SCHOOL (LITERATURE REVIEW) (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores contemporary aspects of organizing physical education lessons in Ukrainian high schools within the context of ongoing social transformations and educational reforms. The overarching aim of secondary education is to cultivate a harmonious and socially responsible personality capable of lifelong learning, self-development, and civic engagement, with a strong awareness of national identity and readiness to defend democratic values. Physical education plays a crucial role in this process, not only as a tool for preserving health and improving physical fitness, but also as a means of developing intellectual, emotional, and social competencies that are vital for modern youth.Particular emphasis is placed on adolescents aged 16–17, for whom physical education lessons represent both a continuation of previously acquired motor skills and a foundation for shaping conscious, value-oriented attitudes toward health and active lifestyles. The study highlights that the curriculum content must be directed toward the formation of key competences: social, motivational, cognitive, functional, technological, professionally applied, and personal. Such competences reflect the multidimensional demands of physical culture and sport, supporting broader socialization and readiness for adult life.The paper underscores the integrative role of physical education in high school, advocating for continuity, integrity, and a student-centered approach in the teaching process. These principles ensure the consideration of individual needs, health status, and personal interests of learners. The article stresses the significance of teachers’ professional competence, since educators are not only organizers of motor activities but also facilitators of differentiated learning and intrinsic motivation. A competence-oriented teacher is expected to create engaging, inclusive, and safe learning environments while applying modern pedagogical technologies and innovative modules such as martial arts, aerobics, and dance programs.The findings suggest that modern physical education lessons should combine health-oriented, developmental, and motivational objectives. Moreover, they should strengthen resilience, foster teamwork, and cultivate positive values, including self-discipline, perseverance, and responsibility. The article concludes that effective physical education in senior school represents a strategic factor in shaping harmoniously developed personalities, while future research should focus on adapting international best practices to the Ukrainian educational system.
Keywords: physical education; high school students; competence-based approach; motivation; differentiated learning; physical preparedness; health-oriented activity